3. The Oblique Parallel Perspective of Asian Art - Sofron Daniel (Sciendo, 2023)
This paper examines the use of oblique parallel perspective as a method of structuring pictorial space in Far Eastern art. Unlike the conical perspective of the Renaissance, this type of perspective is not grounded on a scientific foundation; and yet, it follows a series of well-defined principles that offer a rational solution to the problem of representing space. Inspired by the philosophies of the Far East, Asian perspective is a completely different phenomenon, if we compare it to the types of perspective used by European artists. In the 17th century, Asian artists begin experimenting with convergence - an element that is typical of conical perspective. This phenomenon did not take hold, as the attempts to adapt conical perspective did not have an impact on the deeply traditional cultures of the Far East.